2003
DOI: 10.1128/jvi.77.19.10557-10565.2003
|View full text |Cite
|
Sign up to set email alerts
|

Access of Antibody Molecules to the Conserved Coreceptor Binding Site on Glycoprotein gp120 Is Sterically Restricted on Primary Human Immunodeficiency Virus Type 1

Abstract: Anti-human immunodeficiency virus type 1 (HIV-1) antibodies whose binding to gp120 is enhanced by CD4 binding (CD4i antibodies) are generally considered nonneutralizing for primary HIV-1 isolates. However, a novel CD4i-specific Fab fragment, X5, has recently been found to neutralize a wide range of primary isolates.To investigate the precise nature of the extraordinary neutralizing ability of Fab X5, we evaluated the abilities of different forms (immunoglobulin G [IgG], Fab, and single-chain Fv) of X5 and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
333
5
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(354 citation statements)
references
References 66 publications
15
333
5
1
Order By: Relevance
“…These findings distinguish the neutralization activity of D5-IgG1 from that of X5-IgG1, which showed poor activity against isolates other than HXB2 (23). Importantly, D5-IgG1 did not block infectivity of HIV pseudotyped with the vesicular stomatitis virus-G protein (Table 1), supporting the conclusion that the antiviral target of D5-IgG1 is the HIV envelope glycoprotein.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These findings distinguish the neutralization activity of D5-IgG1 from that of X5-IgG1, which showed poor activity against isolates other than HXB2 (23). Importantly, D5-IgG1 did not block infectivity of HIV pseudotyped with the vesicular stomatitis virus-G protein (Table 1), supporting the conclusion that the antiviral target of D5-IgG1 is the HIV envelope glycoprotein.…”
Section: Resultssupporting
confidence: 52%
“…Previous reports found that the HIV-neutralizing activity of the X5 scFv was dramatically reduced upon conversion to an IgG, presumably because the larger IgG could not gain access to its binding site (23). Unlike X5, the human IgG1 form of D5 retained antiviral activity against HIV in both the HIVRP (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…A vaccine capable of protecting cats against infection with a wide range of virulent primary isolates remains a challenge, primarily because of the limited number of conserved neutralization epitopes that have been identified and the failure to present such epitopes appropriately in vaccines. Steric factors may render neutralization epitopes inaccessible to NAbs (Chiarantini et al, 1998;Labrijn et al, 2003), whilst most of the antibodies generated by vaccination may be directed against non-neutralizing epitopes (Dhillon et al, 2007;Richman et al, 2003). Accordingly, the identification of conserved determinants for neutralization will be an important advance in the design of the next generation of FIV vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…A vaccine capable of protecting cats against infection with a wide range of virulent primary isolates remains a challenge, primarily because of the limited number of conserved neutralization epitopes that have been identified and the failure to present such epitopes appropriately in vaccines. Steric factors may render neutralization epitopes inaccessible to NAbs (Chiarantini et al, 1998;Labrijn et al, 2003), whilst most of the antibodies generated by vaccination may…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation